Field notes contributed by Aaron Brees, fall 1998 - Brees, Aaronet al (1998)
Fall report of birds and locations contributed by Aaron Brees. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1998. Epson - sheet feed/flatbed